ENGLISH AND INDONESIAN GREETINGS AS ADJACENCY PAIRS: A PRAGMATIC STUDY - Arni Arsyad Sultan (UIN Alauddin Makassar, 2020)
A speaker customarily opens the conversation by saying greeting to his or her interlocutor. At a glance, greetings maybe not a complicated activity but for the most part, they are highly conventionalized and follow patterned routines. Despite it, the pattern or sequence of greetings along with its type is dynamic and developed. The research aimed to describe the kinds of verbal and non-verbal greetings customarily shown in every exchange, to reveal the sequence of English and Indonesian greetings as adjacency pairs in social exchange. The data consists of English collected from